Risk factors for recovery of Imipenem-or ceftazidime-resistant Pseudomonas aeruginosa among patients admitted to a teaching hospital in Brazil - Fortaleza, Carlos Magno Castelo Branco [UNESP]; Freire, Maristela P.; Filho, Djalma de C. Moreira; de Carvalho Ramos, Marcelo (Univ Chicago Press, 2006)
background. The prevalence of resistance to imipenem and ceftazidime among Pseudomonas aeruginosa isolates is increasing worldwide.objective. Risk factors for nosocomial recovery ( defined as the finding of culture- positive isolates after hospital admission) of imipenemresistant P. aeruginosa ( IRPA) and ceftazidime- resistant P. aeruginosa ( CRPA) were determined.design. Two separate case- control studies were conducted. Control subjects were matched to case patients ( ratio, 2: 1) on the basis of admission to the same ward at the same time as the case patient. Variables investigated included demographic characteristics, comorbid conditions, and the classes of antimicrobials used.setting. The study was conducted in a 400- bed general teaching hospital in Campinas, Brazil that has 14,500 admissions per year. Case patients and control subjects were selected from persons who were admitted to the hospital during 1992 - 2002.results. IRPA and CRPA isolates were obtained from 108 and 55 patients, respectively. Statistically significant risk factors for acquisition of IRPA were previous admission to another hospital ( odds ratio [ OR], 4.21 [ 95% confidence interval {CI}, 1.40- 12.66];), hemodialysis Pp. 01 ( OR, 7.79 [ 95% CI, 1.59- 38.16];), and therapy with imipenem ( OR, 18.51 [ 95% CI, 6.30- 54.43];), amikacin ( OR, 3.22 Pp. 01 P !.001 [ 95% CI, 1.40- 7.41];), and/ or vancomycin ( OR, 2.48 [ 95% CI, 1.08- 5.64];). Risk factors for recovery of CRPA were Pp. 005 Pp. 03 previous admission to another hospital ( OR, 18.69 [ 95% CI, 2.00- 174.28];) and amikacin use ( OR, 3.69 [ 95% CI, 1.32- 10.35]; Pp. 01). Pp. 01conclusion. Our study suggests a definite role for several classes of antimicrobials as risk factors for recovery of IRPA but not for recovery of CRPA. Limiting the use of only imipenem and ceftazidime may not be a wise strategy to contain the spread of resistant P. aeruginosa strains.